Association between occupational exposure to mineral oil and rheumatoid arthritis: results from the Swedish EIRA case–control study - Sverdrup, Berit (BioMed Central, 2005)
The aim of the present study was to investigate the association between exposure to mineral oil and the risk of developing rheumatoid arthritis (RA), and in addition to perform a separate analysis on the major subphenotypes for the disease; namely, rheumatoid factor (RF)-positive RA, RF-negative RA, anticitrulline-positive RA and anticitrulline-negative RA, respectively. A population-based case–control study of incident cases of RA was performed among the population aged 18–70 years in a defined area of Sweden during May 1996–December 2003. A case was defined as an individual from the study base who for the first time received a diagnosis of RA according to the American College of Rheumatology criteria of 1987. Controls were randomly selected from the study base with consideration taken for age, gender and residential area. Cases (n = 1,419) and controls (n = 1,674) answered an extensive questionnaire regarding lifestyle factors and occupational exposures, including different types of mineral oils. Sera from cases and controls were investigated for RF and anticitrulline antibodies. Among men, exposure to any mineral oil was associated with a 30% increased relative risk of developing RA (relative risk = 1.3, 95% confidence interval = 1.0–1.7). When cases were subdivided into RF-positive RA and RF-negative RA, an increased risk was only observed for RF-positive RA (relative risk = 1.4, 95% confidence interval 1.0–2.0). When RA cases were subdivided according to the presence of anticitrulline antibodies, an increased risk associated with exposure to any mineral oil was observed only for anticitrulline-positive RA (relative risk = 1.6, 95% confidence interval = 1.1–2.2). Analysis of the interaction between oil exposure and the presence of HLA-DR shared epitope genes regarding the incidence of RA indicated that the increased risk associated with exposure to mineral oil was not related to the presence of shared epitope genotypes. In conclusion, our study shows that exposure to mineral oil is associated with an increased risk to develop RF-positive RA and anticitrulline-positive RA, respectively. The findings are of particular interest since the same mineral oils can induce polyarthritis in rats.